Analysis of Habib Husein Ja'far "Jeda Nulis" Podcast as a Medium of Dakwah Against Young Generation on Era 4.0 - Bella Munita Sary; Masayu Fatiyah Nuraziimah; Nurhasanah Walijah (Proceeding of International Conference on Islamic Education, 2021)
The rapid development of technology has had a massive impact in the use of new media in various parts of the world. Its goal is to help for making it easier for people to live their daily lives. One of the new media that has recently become a favorite of the public, especially in Indonesia is a podcast. In Indonesia, a Youtube podcast channel "Jeda Nulis" owned by Habib Husein Ja'far Al Hadar or Habib Ja'far is a new favorite among young adults. Habib Ja'far not only uses Youtube for its Jeda Nulis podcast, but also Spotify. This study aims to analyze the Jeda Nulis podcast and observes people’s responses to the Islamic da'wah strategy introduced by Habib Ja’far. The method used in this research is a literature review that includes the process of listening to and analyzing podcasts in "Jeda Nulis" YouTube channel as preaching media. The results of this study show that there are pros and cons to this podcast. The pro commentary has liked this podcast because of the way the preaching was delivered by Habib Husein Ja'far as well. On the other hand, there are also people who are uncomfortable with the podcast "Jeda Nulis” in accordance with the content and many people who feel that they are inferior to him.